The short stature homeobox gene SHOX is involved in skeletal abnormalities in Turner syndrome - Clement-Jones, Mark; Wöginger, Simone; Rao, Ercole; Blaschke, Rüdiger Jörg; Zuniga, Aimée; Zeller, Rolf; Robson, Stephen C.; Binder, Gerhard; Glass, Ian; Strachan, Tom; Lindsay, Susan; Rappold, Gudrun (Human molecular genetics, 2000)
Turner syndrome is characterized by short stature and is frequently associated with a variable spectrum of somatic features including ovarian failure, heart and renal abnormalities, micrognathia, cubitus valgus, high-arched palate, short metacarpals and Madelung deformity. Madelung deformity is also a key feature of Leri-Weill syndrome. Defects of the pseudoautosomal homeobox gene SHOX were previously shown to lead to short stature and Leri-Weill syndrome, and haploinsufficiency of SHOX was implicated to cause the short stature phenotype in Turner syndrome. Despite exhaustive searches, no direct murine orthologue of SHOX is evident. SHOX is, however, closely related to the SHOX2 homeobox gene on 3q, which has a murine counterpart, Og12x. We analysed SHOX and SHOX2 expression during human embryonic development, and referenced the expression patterns against those of Og12x. The SHOX expression pattern in the limb and first and second pharyngeal arches not only explains SHOX-related short stature phenotypes, but also for the first time provides evidence for the involvement of this gene in the development of additional Turner stigmata. This is strongly supported by the presence of Turner-characteristic dysmorphic skeletal features in patients with SHOX nonsense mutations.
Gesehen am 24.03.2021